The classification of concentration of mixture of analytes - Baronas, Romas; Ivanauskas, Feliksas; Maslovskis, Romualdas; Vaitkus, Pranas (Lietuvos matematikos rinkinys, 2004)
This paper presents a system which is used for the classification of biosensor signals. The proposed system is applied to the the synthesized and experimental data. The developed system showed good prediction perfomance.